DESIGNING FUNCTIONAL BEVERAGES PROCESS : HIGHLIGHTING LESSONS LEARNED FROM RESEARCH AND DEVELOPMENT - Agus Sudibyo (Balai Besar Industri Hasil Perkebunan, 2018)
In recent times, there has been growing recognition of the key role of foods and beverage in disease prevention and treatment. Rapidly increasing knowledge on nutrition, medicine, and plant biotechnology has dramatically changed the concepts about food, health and agriculture, and brought in revolution of them. Research currently underway at academic, industry and government facilities will reveal how a myriad of substances can be used as functional food components. Thus natural bioactive compounds include a broad diversity of structures and functionalities that provide an excellent pool of molecules for the production of nutraceuticals, functional foods, and food addives. This review attempts to display about research and development of functional beverages and designing functional beverages and the formula for beverage success.Keywords: designing, functional beverages, lessons learned, highlighting, research and development.